Correlation of bone marrow 2-deoxy-2-[18F]fluoro-D-glucose uptake with systemic inflammation in patients with newly diagnosed endometrial cancer. Issue 8 (30th May 2022) - Ishibashi, Megumi; Norikane, Takashi; Yamamoto, Yuka; Imajo, Masashi; Takami, Yasukage; Mitamura, Katsuya; Tanaka, Tamaki; Tsuruta, Tomohiko; Kanenishi, Kenji; Nishiyama, Yoshihiro
Abstract : Objective: To clarify the relationship between 2-deoxy-2-[ 18 F]fluoro-D-glucose (FDG) uptake of bone marrow and systemic inflammation in patients with newly diagnosed endometrial cancer. Methods: A total of 119 patients with untreated endometrial cancer underwent FDG PET/computed tomography (CT). For bone marrow FDG uptake, the mean standardized uptake value (SUVmean) of the five vertebrae (T11-12 and L3-L5) was measured and averaged (bone marrow SUV). The bone marrow-to-liver ratio (BLR) was calculated by dividing the bone marrow SUV by the SUVmean of the normal liver. FDG PET parameters were correlated with white blood cell count, neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and C-reactive protein (CRP), albumin, and hemoglobin levels. They were also correlated with FIGO stage. Results: Bone marrow SUV and BLR showed significant positive correlations with white blood cell count, NLR, and CRP level and significant negative correlations with albumin level. BLR also showed a significant positive correlation with PLR. No significant differences in bone marrow SUV and BLR were apparent according to FIGO stage. Conclusion: Pretreatment FDG PET/CT in patients with newly diagnosed endometrial cancer may provide information on host systemic inflammation as assessed by bone marrow FDG uptake.